The legality of wind and altitude assisted performances in the sprints - Mureika, J. R. (New Studies in Athletics, 2000)
Based on a mathematical simulation which reproduces accurate split and velocity profiles for the 100 and 200 metre sprints, the magnitudes of altitude and mixed wind/altitude-assisted performances as compared to their sea-level equivalents are presented. It is shown that altitude-assisted times for the 200 metre are significantly higher than for the 100 metre, suggesting that the "legality'' of such marks perhaps be reconsidered.